Art against dictatorship : making and exporting arpilleras under Pinochet - Adams, Jacqueline (Louann Atkins Temple women & culture series, 2013)
This study of Chilean arpillera folk art and its makers, sellers, and buyers explores the creation of a solidarity art system and shows how art can be a powerful force for opposing dictatorship and empowering oppressed people.